Investigation of Hygro-Thermal Cycle Effects on the Membranes of Proton Exchange Membrane Fuel Cells - Colak, Ozgen; Acar, Alperen; Ergenekon, Emre (AMER SOC TESTING MATERIALS, 2014)
Nafion is the most commonly used membrane material in proton exchange membrane fuel cells. New and used membrane electrode assemblies (MEAs) are subjected to dynamic mechanical analysis (DMA) tests in temperature scan mode to determine the effect of catalyst coating and hygro-thermal aging. DMA tests are also performed using specimens obtained from the rolling and transverse directions to investigate the anisotropic effects of the membrane and the coating. The catalyst coating increases the stiffness and brittleness of the membrane. Increased stiffness is observed in used MEAs relative to new MEAs, which indicates that hygro-thermal aging increases the brittleness of the material. A slight dependence on direction-that is, anisotropy-is also determined.
Keywords: Nafion; dynamic mechanical analysis; membrane electrode assembly; proton exchange membrane fuel cell; mechanical properties; anisotropy; PERFLUOROSULFONIC ACID; MECHANICAL-PROPERTIES; TEMPERATURE; HYDRATION; HUMIDITY; Materials Science